DIE TEXTE HUMBANNUMENAS. - MADER, Michael (Iranica Antiqua, 2019)
There are three royal inscriptions authored by Humbannumena (c. 1350 BC), one written in Elamite (EKI 4C) and two written in Akkadian (EKI 4B and the Tavernier fragment). All three were found in Liyan. In the present paper, a morpheme analysis is given for EKI 4C. Compared to previous translations, some modifications are proposed, the most consequential of which being the rejection of a sumerian loanword men 'crown' in Elamite: Based on contemporaneous text copies of EKI 4C which read tak-u-me instead of tak-me, the analysis of line IV must be sit tak-(u-)me en pissi-k 'the destiny of my life is established' instead of sitta-k men pissi-k 'prosperity is re-established and the crown is restored'. Various other arguments for the new translation are put forward. As the alleged 'restored crown' had been the starting point for the "usurpator thesis" as well as the "double monarchy thesis", a fresh view on the succession to the throne in the Igihalkid dynasty is necessary.